Pemberdayaan Kader dalam Penatalaksanaan Ibu Hamil Kekurangan Energi Kronis dan Balita Malnutrisi - Tonny Cortis Maigoda; Kusdalinah Kusdalinah; Demsa Simbolon; Ahmad Rizal; Mariati Mariati; Afrina Mizawati (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The problem of malnutrition in children under five starts from malnutrition during pregnancy such as Chronic Energy Deficiency (CED). One of the nutrition improvement programs for pregnant women in Central Bengkulu Regency is Food Supplementary feeding  for CED pregnant women and toddlers, including in Semidang Lagan District, Central Bengkulu Regency. A holistic approach is needed starting from cadres, health workers, communities, partners with local government officials, as well as the private sector in preventing and overcoming the problem of CED pregnant women and malnourished toddlers. Community Service Activities (CSA) were carried out in the villages of Taba Lagan, Pagar Jati and Lagan Bungin with the aim of empowering cadres in managing CED pregnant women and malnourished toddlers. The results of the CSA activity showed that there is an increase in skill score of cadres in anthropometric measurements practices , an increase in the knowledge of mothers having children under five, an increase in the size of the MUAC for CED pregnant women, an increase of cadres ability  to motivate pegnant women with CED  in each villages. Local government support financial assisstance for villages continuously.